2019
DOI: 10.1246/bcsj.20190252
|View full text |Cite
|
Sign up to set email alerts
|

Methylarene-Based PAH Synthesis via Domino Cyclization of 1,1-Difluoro-1-alkenes

Abstract: Polycyclic aromatic hydrocarbons (PAHs) containing 4–7 benzene rings were synthesized via a methylarene-based protocol. Trimethyl[2-(trifluoromethyl)allyl]silane was electrophilically benzylated with Ar1CH2Br (prepared from Ar1CH3) to afford 2-trifluoromethyl-1-alkenes that were in turn nucleophilically benzylated with Ar2CH2Li (prepared from Ar2CH3) through an SN2′-type reaction to produce 1,1-difluoroethylenes, which are cyclization precursors bearing two 2-arylethyl groups. Magic acid efficiently promoted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Notably, chlorinated 13f and brominated 13g underwent hydrodehalogenation as well as dehydrogenation by Pd/C (not shown). 24 Although p -chloranil (tetrachloro- p -benzoquinone) was not effective, triphenylmethylium tetrafluoroborate (Ph 3 CBF 4 ), which was effective in our previous synthesis of angular PAHs, 10c provided 5g from 13g in a moderate yield. The yields of halogenated [4]acenes 5f and 5g were increased by the use of trityl cations, which were generated from triphenylmethyl alcohol in refluxing trifluoroacetic acid.…”
Section: Table 1 Screening Of Lewis Acids (First and Se...mentioning
confidence: 97%
“…Notably, chlorinated 13f and brominated 13g underwent hydrodehalogenation as well as dehydrogenation by Pd/C (not shown). 24 Although p -chloranil (tetrachloro- p -benzoquinone) was not effective, triphenylmethylium tetrafluoroborate (Ph 3 CBF 4 ), which was effective in our previous synthesis of angular PAHs, 10c provided 5g from 13g in a moderate yield. The yields of halogenated [4]acenes 5f and 5g were increased by the use of trityl cations, which were generated from triphenylmethyl alcohol in refluxing trifluoroacetic acid.…”
Section: Table 1 Screening Of Lewis Acids (First and Se...mentioning
confidence: 97%
“…Based on designing distinct reaction manifolds that harness a consecutive vinylic C-F bond breaking, a practical function of gem-difluoroalkene as a readily available onecarbon synthon was previously found by Ichikawa and coworkers (Scheme 59). 106,107 The research highlighted that polycyclic aromatic hydrocarbons (PAHs) could be easily prepared by treating functionalized gem-difluoroalkenes bearing two tethered aryl moieties with magic acid (FSO 3 H•SbF 5 ) or TiF 4 in 1,1,1,3,3,3-hexafluoropropan-2-ol (HFIP). A plausible reaction mechanism revealed that the protonation of difluoroalkene 59-1/monofluoroarene 59-4, leading to fluorine-stabilized cationic species 59-3 and arenium ion 59-5, is more likely to be a key process in the formation of the final product.…”
Section: Gem-difluoroalkenementioning
confidence: 99%